2014
DOI: 10.1073/pnas.1416121111
|View full text |Cite
|
Sign up to set email alerts
|

TSG-6 as a biomarker to predict efficacy of human mesenchymal stem/progenitor cells (hMSCs) in modulating sterile inflammation in vivo

Abstract: Significance The clinical trials with human mesenchymal stem/progenitor cells (hMSCs) from bone marrow and other tissues are proceeding even though cultures of the cells are heterogeneous and there is large variability among preparations of hMSCs due to differences among donors, culture conditions, and inconsistent tissue sampling. However, there is currently no in vitro bioassay for the evaluation of hMSC efficacy in vivo. Therefore, the value of the data obtained from current clinical trials may we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
164
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 38 publications
11
164
1
4
Order By: Relevance
“…Recently, observations by our group and others identified TSG-6 as being responsible for the beneficial effects of MSCs in the treatment of disease models of the heart (4), cornea (5,19,32), brain (33), lung (34), and pancreas (35). TSG-6 exerts its antiinflammatory actions through multiple mechanisms, one of which is the modulation of myeloid cells into a tolerogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, observations by our group and others identified TSG-6 as being responsible for the beneficial effects of MSCs in the treatment of disease models of the heart (4), cornea (5,19,32), brain (33), lung (34), and pancreas (35). TSG-6 exerts its antiinflammatory actions through multiple mechanisms, one of which is the modulation of myeloid cells into a tolerogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 We, and others, have shown that hMSCs suppresses excessive sterile inflammation thereby ameliorating lung injury, 5 myocardial infarction, 29 corneal injury 30 or peritonitis, 26 in part due to hMSCs activation and secretion of TSG-6. Recently, Lee et al, 7 have proposed TSG-6 mRNA levels as a biomarker to predict in vivo efficacy in suppressing inflammation of different donor-derived hMSCs prior to use. Consistent with this concept, HCMV infection also inhibited secretion of IL-6 that is known to contribute to the antiinflammatory effects of ASCs in vivo, 6 possibly by inducing T-regulatory cells to secrete IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggests that the therapeutic effects of ASCs are mediated in large part by release of paracrine factors that modulate inflammatory and immune responses or that enhance tissue repair. [5][6][7][8] Additionally, ASCs can differentiate into various tissues including fat, bone and cartilage 9 and thus have potential for regenerative stem cell therapies. 10,11 Despite promising therapeutic potential of ASCs, little is known about their susceptibility to infectious agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The group also showed that the expression level of TSG--6 mRNA could be directly correlated with MSC capacity to reduce inflammation in sterile mouse models of corneal injury, peritonitis, and lung injury [208]. In a type 1 diabetic mouse model, TSG--6 secreted by MSC was shown by others to inhibit the activation of antigen presenting cells, as well as T cells, and effectively delaying the onset of type 1 diabetes [209].…”
Section: Immune Modulatory Properties Of Mscmentioning
confidence: 96%